Transcriptional Programming in Arteriosclerotic Disease: A Multifaceted Function of the Runx2 (Runt-Related Transcription Factor 2). Issue 1 (January 2021) - Chen, Yabing; Zhao, Xinyang; Wu, Hui
Abstract : Despite successful therapeutic strategies in the prevention and treatment of arteriosclerosis, the cardiovascular complications remain a major clinical and societal issue worldwide. Increased vascular calcification promotes arterial stiffness and accelerates cardiovascular morbidity and mortality. Upregulation of the Runx2 (Runt-related transcription factor 2), an essential osteogenic transcription factor for bone formation, in the cardiovascular system has emerged as an important regulator for adverse cellular events that drive cardiovascular pathology. This review discusses the regulatory mechanisms that are critical for Runx2 expression and function and highlights the dynamic and complex cross talks of a wide variety of posttranslational modifications, including phosphorylation, acetylation, ubiquitination, and O-linked β-N-acetylglucosamine modification, in regulating Runx2 stability, cellular localization, and osteogenic transcriptional activity. How the activation of an array of signaling cascades by circulating and local microenvironmental factors upregulates Runx2 in vascular cells and promotes Runx2-mediated osteogenic transdifferentiation of vascular smooth muscle cells and expression of inflammatory cytokines that accelerate macrophage infiltration and vascular osteoclast formation is summarized. Furthermore, the increasing appreciation of a new role of Runx2 upregulation in promoting vascular smooth muscle cell phenotypic switch, and Runx2 modulated by O -linked β-N-acetylglucosamine modification and Runx2-dependent repression of smooth muscle cell-specific gene expression are discussed. Further exploring the regulation of this key osteogenic transcription factor and its new perspectives in the vasculature will provide novel insights into the transcriptional regulation of vascular smooth muscle cell phenotype switch, reprograming, and vascular inflammation that promote the pathogenesis of arteriosclerosis.